Adipose Tissue is a Potential Source of Hyperandrogenism in Obese Female Rats. Issue 7 (14th June 2018) - Wagner, Isabel Viola; Sahlin, Lena; Savchuk, Iuliia; Klöting, Nora; Svechnikov, Konstantin; Söder, Olle
Abstract : Objective: Obesity in females is often associated with metabolic complications and hyperandrogenism, but the sources of androgens are not completely understood. Therefore, this study investigated whether adipose tissue could be a source of androgens promoting hyperandrogenism development in obese female rats. Methods: Gene expression of steroidogenic enzymes and testosterone levels were determined in periovarian and inguinal adipose tissue and in the supernatant of cultured preadipocytes and adipocytes. The conversion of pregnenolone to androgens was analyzed by thin‐layer chromatography. Results: Substantial amounts of testosterone in adipose tissue (25‐153 ng/g tissue) and in the supernatant of adipocytes (0.33‐0.69 ng/ten thousand cells]) were found. StAR and steroidogenic enzymes encoded by genes including Cyp11A1, Cyp17A1, Cyp19, Hsd3b2, Hsd17b3, and Srd5a2 were expressed in adipose tissue and cultured cells. Thin layer chromatography data revealed that preadipocytes and adipocytes were able to convert pregnenolone to testosterone. Higher levels for all steroidogenic enzymes were found in both depots of obese animals compared with lean animals, with significantly higher levels in inguinal tissue. Conclusions: The whole steroidogenic machinery and capacity for testosterone biosynthesis were found in fat depots of female rats. These findings support the hypothesis that adipose tissue may contribute substantially to the hyperandrogenism in female obesity.